'A Tale of Two Cities': The transition of the electricity sector - Sims, Ralph (Sens public)

(untitled) (Département des littératures de langue française, 2010)
There is no doubt that the issue of environment has become one of the most important of our generation. Whether people contest global warming with passion or want to preserve planet Earth with the most radical methods, the issue generates ardent debates that leave no one indifferent. After having spent nearly four years at the International Energy Agency in Paris, Ralph E. H. Sims has recently returned to his position as Professor of Sustainable Energy and Director of the Centre for Energy Research at Massey University in New Zealand. He is also an IPCC (Intergovernmental Panel on Climate Change) Co-ordinating Lead Author for several IPCC reports covering energy supply, integration and transport. In an essay based on a solid knowledge of the environmental issues and written with a dose of imagination and a touch of humour, he offers his perspectives on a rather dark future for those who prefer the status quo and a brighter one for those who defend a vigorous action in favour of the environment.